Kerangka Sinergi Kebijakan, Teknologi WtE, dan Prinsip ESG untuk Percepatan Bioenergi Sampah Perkotaan di Indonesia - Rudi Haryanto Simanjuntak; Rienni Manihuruk; Mila Viendyasari; Mohammad Syukri (Universitas Perjuangan Tasikmalaya, 2026)
The transition to a low-carbon energy system in Indonesia requires the integration of policies, appropriate conversion technologies, and sustainable financing mechanisms. Municipal solid waste is a strategic bioenergy resource due to its high volume and significant organic content, but the implementation of Waste-to-Energy projects is hampered by a lack of synergy linking policy, technology, and investment aspects. This study aims to formulate a tri-pillar synergy framework between national energy policy, Waste-to-Energy technology suitability, and Sustainable Investment principles (Environmental, Social, and Governance) to overcome these obstacles and accelerate the development of waste-based bioenergy. This study uses a conceptual approach through a comprehensive literature synthesis related to energy regulations, waste management policies, and empirical studies of Waste-to-Energy. The resulting synergy framework identifies that project success is highly dependent on tying price guarantees through policies with social acceptance and risk mitigation through Sustainable Investment principles, which then validates the selection of technologies that are appropriate to the characteristics of local waste in Indonesia. This framework provides a practical contribution in the form of a roadmap for stakeholders in realizing projects that are financially viable, environmentally sustainable, and socially acceptable, while supporting the achievement of renewable energy targets and Sustainable Development Goals in Indonesia.